The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/ani13233705
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Broad Bean Diet on the Growth Performance, Muscle Characteristics, Antioxidant Capacity, and Intestinal Health of Nile Tilapia (Oreochromis niloticus)

Xiaogang He,
Haoming Shu,
Tian Xu
et al.

Abstract: Four crisping diets were designed to conduct a feeding experiment to investigate the use of broad bean in the formulated feed of Nile tilapia and optimize its use. The growth performance, muscle characteristics, antioxidant capacity, and intestinal health of Nile tilapia with an initial body weight of 617.32 ± 1.64 g were evaluated after being fed with different diets for 90 days. The results showed no adverse effect on the growth performance of Nile tilapia fed with broad bean diets. Contrastingly, some impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 59 publications
(66 reference statements)
1
3
0
Order By: Relevance
“…Combined with these findings, it is indicated that FO, SO and RO could increase muscle hardness and springiness by decreasing Cath-B and Cath-L amounts in largemouth bass (Figure 7). In addition, hardness and chewiness are also closely related to muscle fiber diameter and density [96]. Our results found that there was a higher muscle fiber density and smaller muscle fiber diameter, as well as greater muscle hardness in the dorsal muscle of the FO, SO and RO trial groups, which is similar to previous results in glass carp [97] and Nile tilapia [96].…”
Section: Muscle Qualitysupporting
confidence: 89%
See 3 more Smart Citations
“…Combined with these findings, it is indicated that FO, SO and RO could increase muscle hardness and springiness by decreasing Cath-B and Cath-L amounts in largemouth bass (Figure 7). In addition, hardness and chewiness are also closely related to muscle fiber diameter and density [96]. Our results found that there was a higher muscle fiber density and smaller muscle fiber diameter, as well as greater muscle hardness in the dorsal muscle of the FO, SO and RO trial groups, which is similar to previous results in glass carp [97] and Nile tilapia [96].…”
Section: Muscle Qualitysupporting
confidence: 89%
“…In addition, hardness and chewiness are also closely related to muscle fiber diameter and density [ 96 ]. Our results found that there was a higher muscle fiber density and smaller muscle fiber diameter, as well as greater muscle hardness in the dorsal muscle of the FO, SO and RO trial groups, which is similar to previous results in glass carp [ 97 ] and Nile tilapia [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations